Recent advances in acyl radical enabled reactions between aldehydes and alkenes. Issue 50 (11th June 2021) - Liu, Yi-Lin; Ouyang, Yue-Jun; Zheng, Hongxing; Liu, Hongxin; Wei, Wen-Ting
Abstract : Acyl radical enabled reactions between aldehydes and alkenes. Abstract : Radical-mediated functionalization of alkenes has been emerging as an elegant and straightforward protocol to increase molecule complexity. Moreover, the abstraction of a hydrogen atom from aldehydes to afford acyl radicals has evolved as a rising star due to its high atom-economy and the ready availability of aldehydes. Considering the great influence and synthetic potential of acyl radical enabled reactions between aldehydes and alkenes, we provide a summary of the state of the art in this field with a specific emphasis on the working models and corresponding mechanisms. The discussion is divided according to the kind of alkenes and reaction type.